Patient care problems after a heart attack - clinical case study - Sikora, Kamil; Wawryniuk, Agnieszka; Łuczyk, Robert Jan; Zwolak, Agnieszka; Łuczyk, Marta; Nowicka, Elżbieta (Journal of Education, Health and Sport, 2019)
Introduction. Half of deaths in Poland are caused by cardiovascular diseases. Such a high percentage causes them to rank first among the causes of death. According to the Polish Cardiac Society, acute coronary syndromes are the reason for hospitalization of 140,000 people annually, including myocardial infarction of 90,000 people each year [4]. In addition to sudden cardiac deaths, cardiovascular disease is also a major cause of hospitalization, as well as permanent or temporary disability, both physical and mental. This condition has consequences in the form of, among others, inability to work, which leads to the gradual development of social disability [7]. The multitude and variety of problems faced by patients determines the need to recognize and eliminate them. The aim of the study is to present the required scope of patient care after myocardial infarction, based on individual case study. A case report. A 82-year-old patient admitted to hospital after losing consciousness while working in the garden. The ECG showed myocardial ischaemia without visible ST segment elevation. Coronary angiography in the hemodynamic laboratory revealed stenosis of the left coronary artery, which was cleared by the introduction of a vascular stent. An individual care plan has been developed for the patient in accordance with the problems encountered. Conclusions. Patients after myocardial infarction have numerous nursing problems, which require professional actions performed by a nurse, which results in minimizing the problems and their consequences. Thanks to these activities, the patient and his immediate surroundings are prepared to continue providing care in the home environment.